Toward Nitrite-Free Curing: Evaluation of a New Approach to Distinguish Real Uncured Meat from Cured Meat Made with Nitrite - Juan de Dios Hernández; Ana Castell; Natalia Arroyo-Manzanares; Isidro Guillén; Pascuali Vizcaíno; Ignacio López-García; Manuel Hernández-Córdoba; Pilar Viñas (Foods, 2021)
After the International Agency for Research on Cancer (IARC) classified ingested nitrites and nitrates as “probably carcinogenic to humans” under conditions favoring endogenous nitrosation, several meat products labeled as “made without nitrite” were launched. In order to distinguish uncured products truly made without nitrite from cured products made with any nitrite source (vegetal or mineral), this article presents an approach to detect and quantify nitrite from different origins added to meat. The method consists on the determination of nitrous oxide as a target compound using headspace gas chromatography–mass spectrometry (HS-GC–MS). Nitrous oxide (N2O) is formed after two reduction steps: from nitrite to nitric oxide (NO) and then to N2O. The NO is bound to myoglobin (Mb) or metmyoglobin (Met-Mb), forming a complex, which is subsequently released using sulfuric acid, which also favors the reduction to N2O. The HS-GC–MS conditions were split ratio 1:10; injection temperature at 70 °C; incubation temperature at 30 °C and time 45 min; and injection volume 1 mL. As a result, a relationship was established between the concentration of nitrite in cooked ham samples and the area of the N2O peak generated, meaning that this method allows the quantification of added nitrite within a concentration range of 10 to 100 mg kg−1.